A case of Lassa fever: experience at St Thomas's Hospital. Issue 6347 (9th October 1982) - Cooper, C B; Gransden, W R; Webster, M; King, M; O'Mahony, M; Young, S; Banatvala, J E
Abstract : An 18-year-old Nigerian girl, normally resident in Jos, was admitted to hospital for five days before she was diagnosed as having Lassa fever. There were several atypical features in the early stages of here illness, notably the absence of prostration, pharyngitis, or bradycardia and the development of appreciable leucocytosis. Consequent control and surveillance measures required checks for 21 days on 173 people who had had contact with as first line if they had handled her or specimens without taking precautions to avoid direct skin contact with her excretions, secretions, and blood; other contacts were categorised as second line. During her time in hospital she was managed in a single room on a general ward. She visited a number of investigative departments within the hospital, and her specimens were examined in five clinical laboratories. Despite this no secondary cases occurred among either first- or second-line contacts, and there was no serological evidence of subclinical infection among any of the contacts tested (159 people).